2013
DOI: 10.5047/eps.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Giant pulsations as modes of a transverse Alfvénic resonator on the plasmapause

Abstract: The paper assumes that the giant pulsations are oscillations trapped within a resonator resulting from finite plasma pressure on the outer edge of the plasmapause. This resonator is bounded, across the L-shells, by two turning points allowing the wave energy to be channeled azimuthally. This assumption can explain the basic properties of the giant pulsations: strong localization across magnetic shells, poloidal polarization, presence of a significant compressional component in the Pg magnetic field, the fact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
7

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 66 publications
1
24
0
7
Order By: Relevance
“…The trough in the Alfvén speed profile forms a resonance in the similar way of forming the ionospheric Alfvén resonator at several thousand kilometers above Earth [ Lysak , ]. Mode trapping near the plasmapause has been theoretically considered [ Klimushkin , ; Lee and Kim , ; Leonovich and Mazur , ; Klimushkin et al , ; Mager and Klimushkin , ]. Takahashi et al [, ] provide observation evidence of compressional Pc4 waves trapped by the plasmapause on the dayside.…”
Section: Introductionmentioning
confidence: 99%
“…The trough in the Alfvén speed profile forms a resonance in the similar way of forming the ionospheric Alfvén resonator at several thousand kilometers above Earth [ Lysak , ]. Mode trapping near the plasmapause has been theoretically considered [ Klimushkin , ; Lee and Kim , ; Leonovich and Mazur , ; Klimushkin et al , ; Mager and Klimushkin , ]. Takahashi et al [, ] provide observation evidence of compressional Pc4 waves trapped by the plasmapause on the dayside.…”
Section: Introductionmentioning
confidence: 99%
“…During the main phase of an intense geomagnetic storm, Pilipenko et al [, ] was able to use ground magnetometers to identify high‐ m waves among Pi3 pulsations, where Pi3 waves can be the ground counterparts of Pc5 pulsations observed using satellites, as was found in Vaivads et al [] for Ps6 waves, a variety of Pi3 wave. It is possible for large amplitude waves with moderately large azimuthal wave numbers, (| m |=15–40), such as giant pulsations, Pg [e.g., Chisham , ; Chisham et al , ; Mager and Klimushkin , ], to overcome the screening of the ionosphere in order to be observed by ground magnetometers. The westward phase velocity of ground Pg, Pi3, and Ps6 pulsations, like the majority of poloidal pulsations observed by spacecraft is consistent with the idea that the energy source of high‐ m waves is within populations of westward drifting energetic protons.…”
Section: Introductionmentioning
confidence: 99%
“…By studying a few wave events with the Active Magnetospheric Particle Tracer Explorers/Ion Release Module data, Denton et al [] found observational support to this global poloidal mode theory and considered that the dip in poloidal frequency might result from the L dependence of the equilibrium density or magnetic field. More recently, this region where wave energy can be trapped is also called the “transverse Alfvénic resonator,” which can exist not only in the ring current region but also near the plasmpause as well [ Mager and Klimushkin , ; Yeoman et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…The most promising theory to explain such a feature is proposed by Chen [1994, 1996], who show that an energetically trapped global poloidal mode can exist in a region in which the poloidal Alfvén frequency is lower than the toroidal frequency and where it exhibits a dip (minimum) with respect to L. By studying a few wave events with the Active Magnetospheric Particle Tracer Explorers/Ion Release Module data, Denton et al [2003] found observational support to this global poloidal mode theory and considered that the dip in poloidal frequency might result from the L dependence of the equilibrium density or magnetic field. More recently, this region where wave energy can be trapped is also called the "transverse Alfvénic resonator," which can exist not only in the ring current region but also near the plasmpause as well [Mager and Klimushkin, 2013;Yeoman et al, 2012].…”
Section: Introductionmentioning
confidence: 99%